Evaluasi Program Pembinaan Latihan Bola Tangan Kabupaten Sumenep - Ufairah, Nabila Nur; Wahyudi, Heri; Widodo, Achmad; Fithroni, Hijrin (Jurnal Porkes, 2024)
The purpose of this study was to examine the level of success of the ABTI Sumenep District training coaching program for athletes and the application and achievement of the training program obtained by male and female athletes. This study uses the CIPP program evaluation model using a mix of qualitative and quantitative methods. This training coaching program evaluation research uses observation, questionnaire, interview and documentation methods. The results of the CIPP program research get good criteria. with the results of context 3.25 (good), input 2.84 (good), process 3.28 (very good), product 2.81 (good), and the results of the CIPP evaluation 3.04 with good criteria. The conclusion is that the context component that evaluates a handball training coaching program is categorized as good. With indicators of excellent coaching program background, good coaching program goals, and the coaching program is also good. The input component, good with indicators of human resources in good categories, the coach program is very good, funding is good, facilities and infrastructure are good, and parental support is still lacking. The process component, very good with indicators of good implementation, very good coordination, and good monitoring. The product component is good with good achievement indicators.